Interactive multimedia based on autoplay media studio 8 for chemistry on rate of reaction topics for class Xi SMA/Ma - Roza Linda; Herdini Herdini; Zera Rahmaputri (Pascasarjana Universitas Negeri Medan, 2017)
A valid and practical learning Interactive Multimedia of Autoplay Media Studio 8 for Rate of Reaction topics has been developed. The research method was Research and Development with Plomp model which consist of 4 steps; Prelimenary Investigation, Design, Realization, and Validation, evaluation, revision. Media was validated by three validators and limited trial by practitioners (users). The results showed an average score of validation was 96.12%. Based on questionnaire responses of 3 teachers and 20 students each earned an average score of 96.25% and 94.5%, respectively. From the results of the average validation score and limited trial score of Autoplay media studio 8 Interactive Multimedia for Rate of Reaction topics was valid and can be used as a learning media.Key words: autoplay media studio 8, interactive multimedia, rate of reaction